Latihan passing bola digantung dapat Meningkatkan kemampuan mengontrol bola dalam permainan sepak takraw - Nurdin Nurdin (Universitas Pendidikan Mandalika, 2019)
The problem that occurs in this study is the lack of students' ability when passing control the ball while playing sepak takraw. Researchers try to apply the form of exercise to solve existing problems, wherein this exercise refers to passing control the ball requires the right abilities and techniques. The formulation of the problem in this study is whether there is the effect of hanging ball passing exercises on the ability to control the ball in sepak takraw on extracurricular students of SMPN 1 Brang Ene in Academic Year 2019. The purpose of this study was to determine whether or not there was an effect of hanging ball passing exercises on the ability controlling the ball in sepak takraw on Extracurricular students of SMPN 1 Brang Ene in the Academic Year 2019. This study used an experimental method with one group pretest-posttest design. The population in this study were 15 extracurricular students at SMPN 1 Brang Ene. The technique of collecting data uses an act test. Data analysis techniques using the t test. The results of data analysis obtained a t-count of 4.771 t-table with db = 14 and a 5% significance level apparently obtained a t-table of 2.145. This means t-count is greater than t-table or 4.771> 2.145. So the conclusions from this study are significant, so the conclusions of this study are: Ada ’There is the effect of passing training with the ball being hung and paired passing on the ability to control the ball in the soccer takraw game on extracurricular students at SMPN 1 Brang Ene School Year 2019